Education in India 1964-65 Vol. I-Report - Planning Commission (Planning Commission, 1964)
Under the Constitution of India, education for the most part is controlled by the State Governments. The Union Government is responsible for the maintenance of four Central Universities at Aligarh, Banaras, Delhi and Shantiniketan (West Bengal), nine institutions of national importance and the institutions for technical and vocational training. The Union Government is also responsible for the promotion of research and co-ordination and determination of standards in higher education and research. The promotion of education and welfare of the weaker sections of the community is a special responsibility of the Government of India. Another important function of the Union Government is the collection and dissemination of educational information pertaining to the country as a whole and for all programmes of international collaboration in the sphere of education.
Ministry of Education and Youth Services Government of India
Ministry of Education and Youth Services Government of India